PENERAPAN MODEL PEMBELAJARAN MISSOURI MATHEMATIC PROJECT (MMP) UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Muhsin Muhsin; Husna Husna; Putri Raisah (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2020)
Mathematical learning activities are mostly carried out independently with limited guidance from the teacher. This raises the consequences of the demands for student independence in learning. Independence of student learning in the learning process will affect student learning outcomes, students who are independent in learning will enjoy working on problems independently. In fact, not all students have a sense of awareness to be independent in learning, sometimes even during the learning process, students often feel bored and lazy. This may be caused due to the lack of approaches and learning models used by educators. One solution to improve student learning independence through the Missouri Mathematics Project (MMP) learning model. The purpose of this study was to determine the increase in students' learning independence. The population in this study were all eighth grade students of Junior High School 4 Sakti. Sampling using Purposive Sampling class VIII1 was selected as an experimental class and class VIII3 as a control class. The instruments used in the form of an initial test (pretest) and final test (posttest) and a questionnaire of student learning independence. Data processing was performed using SPSS 16.0 using t-test statistics, namely independent sample T-test at a significant level of 0.05. From the results of data processing it is obtained that p-value = 0.001, because p-value <0.05 then H0 is rejected H1 is accepted. Thus it can be concluded that the application of the Missouri Mathematics project (MMP) learning model can improve the learning independence of eighth grade students of Junior High School 4 Sakti. Abstrak Kegiatan pembelajaran matematika sebagian besar dilakukan secara mandiri dengan bimbingan terbatas dari guru. Hal ini memunculkan konsekuensi adanya tuntutan kemandirian siswa dalam belajar. Kemandirian belajar siswa dalam proses belajar akan mempengaruhi hasil belajar siswa, siswa yang mandiri dalam pembelajaran akan senang mengerjakan soal secara mandiri. Pada kenyataannya tidak semua siswa memiliki rasa kesadaran untuk mandiri dalam belajar, bahkan kadang saat proses belajar berlangsung, siswa sering merasa bosan dan malas. Hal ini mungkin di sebabkan karena minimnya pendekatan dan model pembelajaran yang digunakan oleh pendidik. Salah satu solusi untuk meningkatkan kemandirian belajar siswa melalui model pembelajaan Missouri Mathematics Project (MMP). Tujuan dalam penelitian ini adalah untuk mengetahui peningkatan kemandirian belajara siswa. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 4 Sakti. Penarikan sampel menggunakan Purposive Sampling maka terpilih kelas VIII1 sebagai kelas eksperimen dan kelas VIII3 sebagai kelas kontrol. Instrumen yang digunakan berupa tes awal (pretest) dan tes akhir (postest). Pengolahan data dilakukan dengan menggunakan bantuan SPSS 16.0 menggunakan statistik uji-t yaitu independent sampel T-test pada taraf signifikan 0,05. Dari hasil pengolahan data maka diperoleh bahwa p-value=0,001, karena p-value < 0.05 maka H0 ditolak H1 diterima. Dengan demikian dapat disimpulkan penerapan model pembelajaran Missouri Mathematics project (MMP) dapat meningkatkan kemandirian belajar siswa kelas VIII SMP Negeri 4 Sakti. Kata Kunci: Kemandirian Belajar, Missouri Mathematics Project